Implementasi Lesson Study Melalui Model Pembelajaran Problem Solving Untuk Meningkatkan Kemampuan Berpikir Kreatif Dan Hasil Belajar - I Wayan Gunada; Syahrial Ayub; Kesipudin Kesipudin (Department of Physics Education, Universitas Mataram, 2019)
The aim of this research is to improve the quality process, to develop creative thinking, and to create a good result of lesson study by implementing a problem solving method. This research is a class action research which involved 19 physcics students who enroll in matrik and vector space subject at even semester of 2017-2018. The data was collected by employing test and interview. It is analyzed by descriptive method. The result of this problem solving reseach are (1) giving the positive impact towards the ability of creative thinking (2) increasing the result of learning process (3) improving the ability of students to better understand the learning process and the ability to apply this problem solvingÃÂ method in any types of problems, and (4) increasing students' learning activity. Based on the result of this research, it is recommended to implementing the problem solving method in any types of learning. The problem solving method is expected to be the answer of any problems in physics.